2015
DOI: 10.1111/all.12628
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ ability to treat anaphylaxis using adrenaline autoinjectors: a randomized controlled trial

Abstract: BackgroundPrevious work has shown patients commonly misuse adrenaline autoinjectors (AAI). It is unclear whether this is due to inadequate training, or poor device design. We undertook a prospective randomized controlled trial to evaluate ability to administer adrenaline using different AAI devices.MethodsWe allocated mothers of food‐allergic children prescribed an AAI for the first time to Anapen or EpiPen using a computer‐generated randomization list, with optimal training according to manufacturer's instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 18 publications
3
71
1
Order By: Relevance
“…Various EAs may come to market having different mechanisms of activation and variations in ease of use. 53,54 Education about anaphylaxis recognition and injection technique is advised to ensure familiarity with the specific device prescribed.…”
Section: Using Easmentioning
confidence: 99%
“…Various EAs may come to market having different mechanisms of activation and variations in ease of use. 53,54 Education about anaphylaxis recognition and injection technique is advised to ensure familiarity with the specific device prescribed.…”
Section: Using Easmentioning
confidence: 99%
“…As a result, there is a need for training in when and how to use adrenaline in general, and more specifically autoinjectors, among patients, practitioners, and pharmacists [21,22,23,24,25,26]. The use of autoinjectors may be preferred for emergency use by health care professionals in some instances [27].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of newer AAIs such as the next-generation EpiPen, Jext, Emerade and Auvi-Q may impact on future assessments, although the majority of these devices use the same/similar injecting mechanisms. The most recent study in this review compared AAI use between devices and found that when prescribed a new device without receiving specific training, successful administration rates for mothers were higher with Auvi-Q (an audio-prompt AAI) (93%) than other traditional devices (ie, EpiPen, Anapen, Jext) (49%) 15. It is likely that correct administration rates will increase if audio-prompt devices are made readily available.…”
Section: Discussionmentioning
confidence: 99%